(untitled) (Journal of the College of Education for Women, 2020)
Cognitive stylistics also well-known as cognitive poetics is a cognitive approach to language. This study aims at examining literary language by showing how Schema Theory and Text World Theory can be useful in the interpretation of literary texts. Further, the study attempts to uncover how readers can connect between the text world and the real world. Putting it differently, the study aims at showing how the interaction between ‘discourse world’ and ‘text world’. How readers can bring their own experience as well as their background knowledge to interact with the text and make interpretive connections. Schema and text world theories are useful tools in cognitive stylistic studies. The reader’s perception of a particular text world depends on her/his existing schema during the process of interpretation. The selected texts for the study are "Strange Meeting" by Wilfred Owen, "In Winter" by Corbett Harrison and the opening passage of David Lodge’s novel Changing Places which are intended to show how the two theories can be integrated to account for the way in which text worlds are perceived. So as a result, readers start establishing meaning based on their schemata and these meanings change through adding a new one. The cognitive ability to understand literary texts and how readers build mind worlds is a crucial aim in cognitive poetics. An in-depth cognitive stylistic analysis reveals significant points about reading and interpreting the selected literary texts by providing a way of thinking about background knowledge and how the individual’s experience would influence their interpretation and viewing of the text world.